(untitled) (Research, Society and Development, 2023)
Environmental education is of fundamental importance, as it allows the solution of various problems in our lives and new ideas for the community. Thus, this article aims to investigate the conceptions of high school students about recycling and waste management in their homes, as well as to analyze their knowledge about the causes and damages of solid waste disposal in the environment. Based on this premise, the methodology adopted in the work sought to contemplate different questions, in order to identify the habits and knowledge of students with regard to solid waste in post-consumption, but also in an earlier moment, which is conscious consumption. Thus, seeking to create a critical awareness, demonstrating that waste involves environmental, economic, social and ethical aspects, therefore fundamental for the good coexistence of all. The answers found in the questionnaire applied to the students allowed us to perceive that they have a critical environmental education regarding the theme of solid waste, mainly linked to the knowledge of garbage and its destination within their community.